Fear and loathing in Las Vegas [videorecording (Blu-Ray)] - Gilliam, Terry; Grisoni, Tony; Davies, Tod, 1955-; Cox, Alex, 1954-; Depp, Johnny; Toro, Benicio del, 1967-; Diaz, Cameron; Ricci, Christina; Barkin, Ellen, 1954-; Maguire, Tobey, 1975-; Pecorini, Nicola, 1957-; Thompson, Hunter S. (Criterion collection, 2011)
It is 1971, and journalist Raoul Duke barrels toward Las Vegas, accompanied by a trunkful of contraband and his unhinged Samoan attorney, Dr. Gonzo, to cover a motorcycle race. His cut-and dried assignment quickly descends into a feverish psychedelic odyssey.